2022
DOI: 10.1016/j.bpj.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase dynamics of DNA supercoiling based on DNA polymer physics

Abstract: DNA supercoils are generated in genome regulation processes such as transcription and replication and provide mechanical feedback to such processes. Under tension, a DNA supercoil can present a coexistence state of plectonemic and stretched phases. Experiments have revealed the dynamic behaviors of plectonemes, e.g., diffusion, nucleation, and hopping. To represent these dynamics with conformational changes, we demonstrated first the fast dynamics on the DNA to reach torque equilibrium within the plectonemic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…We cannot simulate a higher diffusion coefficient with the explicit random walk model due to computational limitations. We found no major difference between the two models in the response of mean mRNA production to promoter strength (S15A We also need to point out that our model neglected the complex dynamics of supercoiling, i.e., the different diffusion behavior of the twist and the writhe [63] and the hopping of plectonemes [29]. According to a recent two-phage dynamic model of supercoiling [63], twist diffusion reaches fast equilibrium, compared to the RNAP translocation, while writhe diffusion is slow.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We cannot simulate a higher diffusion coefficient with the explicit random walk model due to computational limitations. We found no major difference between the two models in the response of mean mRNA production to promoter strength (S15A We also need to point out that our model neglected the complex dynamics of supercoiling, i.e., the different diffusion behavior of the twist and the writhe [63] and the hopping of plectonemes [29]. According to a recent two-phage dynamic model of supercoiling [63], twist diffusion reaches fast equilibrium, compared to the RNAP translocation, while writhe diffusion is slow.…”
Section: Discussionmentioning
confidence: 93%
“…We found no major difference between the two models in the response of mean mRNA production to promoter strength (S15A We also need to point out that our model neglected the complex dynamics of supercoiling, i.e., the different diffusion behavior of the twist and the writhe [63] and the hopping of plectonemes [29]. According to a recent two-phage dynamic model of supercoiling [63], twist diffusion reaches fast equilibrium, compared to the RNAP translocation, while writhe diffusion is slow. Meanwhile, the transition from the twisted to the writhed state could happen dynamically during the translocation process [63].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This hypothesis appears to be reasonable, for example, in the case of transcription, whose initiation step requires the formation of a DNA denaturation bubble [30]. Namely, the twist and writhe relaxation times (below 1 ms) for a 10 kb long molecule are typically 5 orders of magnitude smaller than the time for synthesizing a 1 kb long messenger RNA (100 s) [31][32][33] and 2 orders of magnitude with respect to the time for synthesizing a single base pair. Thus, questions concerning the energy required to denature DNA have been systematically addressed in the context of the equilibrium statistical mechanics of one-dimensional systems [29,34,35].…”
Section: Equilibrium Models Of Supercoiled Dnamentioning
confidence: 93%
“…Finally, hypothesis (iv) was made by considering the relaxation speed of the linking number as given by the diffusion speed of plectonemes. However, both single-molecule experiments [45,106] and polymer simulations [31][32][33]51] have shown that the former, which is responsible for the formation of plectonemes, is much higher than the latter. In other words, supercoiling establishment during transcription can be regarded as a quasi-static process [33].…”
Section: Physical Models Of the Ttl Biological Modelmentioning
confidence: 99%